2006
DOI: 10.1002/asna.200510520
|View full text |Cite
|
Sign up to set email alerts
|

Most supermassive black hole growth is obscured by dust

Abstract: Supermassive black holes underwent periods of exponential growth during which we seem them as quasars in the distant Universe. The summed emission from these quasars generates the cosmic X-ray background, the spectrum of which has been used to argue that most black-hole growth is obscured [1−2] .There are clear examples of obscured black-hole growth in the form of 'type-2' quasars [3−5] , but their numbers are fewer than expected from modelling of the X-ray background. Here we report on the direct detection … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
(48 reference statements)
0
5
0
Order By: Relevance
“…Lacy et al (2007) using Spitzer data of six 0.3 < z < 0.8 type-2 quazars found a contribution of the extinction towards the nucleus from an extended star-forming disk on scales of kiloparsecs, in addition to, or instead of, the traditional dusty torus. Moreover, Martínez-Sansigre et al (2006b) also using highredshift type-2 quasars from Spitzer and VLA data of the Spitzer First Look Survey, concluded that the nuclear region could be effectively obscured by dust on large scales, away from the torus. Additionaly, Rigby et al (2006) using X-ray-selected AGN with spectroscopic redshifts in the Chandra Deep Field South (CDFS) argued that part of the column density that obscures the soft Xrays may come from the galactic disk.…”
Section: Why Do Sy1 Nuclei Favour Elliptical Hosts?mentioning
confidence: 99%
See 1 more Smart Citation
“…Lacy et al (2007) using Spitzer data of six 0.3 < z < 0.8 type-2 quazars found a contribution of the extinction towards the nucleus from an extended star-forming disk on scales of kiloparsecs, in addition to, or instead of, the traditional dusty torus. Moreover, Martínez-Sansigre et al (2006b) also using highredshift type-2 quasars from Spitzer and VLA data of the Spitzer First Look Survey, concluded that the nuclear region could be effectively obscured by dust on large scales, away from the torus. Additionaly, Rigby et al (2006) using X-ray-selected AGN with spectroscopic redshifts in the Chandra Deep Field South (CDFS) argued that part of the column density that obscures the soft Xrays may come from the galactic disk.…”
Section: Why Do Sy1 Nuclei Favour Elliptical Hosts?mentioning
confidence: 99%
“…Specifically, according to studies investigating the differences between Sy1's and Sy2's (e.g. Koulouridis et al 2006;Rigby et al 2006;Martínez-Sansigre et al 2006a;Lacy et al 2007;Villarroel et al 2012;Netzer 2015;Bornancini & García Lambas 2018;Zou et al 2019;Bornancini & García Lambas 2020) and the connection with their host galaxies at redshifts 0.03 < z < 0.2 (Villarroel et al 2012;Koulouridis et al 2013), it has been shown that type-1 and type-2 Seyfert galaxies have different optical, mid-IR, X-ray and morphological properties and also reside in statistically different environments (Bornancini & García Lambas 2020). Moreover, it is found that the neighbours of Sy2 AGN are more starforming and bluer than Sy1 AGN (see also Koulouridis et al 2013) and also that Sy2 hosts are surrounded by a larger number of dwarf galaxies (Villarroel et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…• Two possible sources of obscuration-a dusty host or an accretion torus-the latter obviously most relevant to "unification" (Martinez-Sansigre et al 2006). • The existence of "natural born 2's" with no obscuration (Wolter et al 2005).…”
Section: Less Certain Answersmentioning
confidence: 99%
“…By way of an example, SFRs derived from 24-µm fluxes via the infra-red luminosity can be overestimated because of (dominant) contamination by evolved stars (Kennicutt & Evans 2012) or by AGN contamination (see e.g. Martínez-Sansigre et al 2005, Martínez-Sansigre et al 2006).…”
Section: Introductionmentioning
confidence: 99%